Trusting the tides ; self-empowerment through our emotions - "Dickson, Anne" (London, 2000)
Few of us understand our emotions. We can be overwhelmed by anxiety; we confuse grief with depression, anger with aggression. Even when we suspect that various bodily ailments are connected with our emotions, we don't know how to help ourselves.
Keywords: Self-Empowerment